2023
DOI: 10.3344/kjp.22336
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of chronic pain and contributing factors: a cross-sectional population-based study among 2,379 Iranian adolescents

Abstract: Background: This study aimed to determine the prevalence of chronic pain and its contributing factors among teenagers aged 12-21 years in Shiraz, Iran. Methods: This cross-sectional study was conducted on adolescents aged 12-21 years. Demographic variables of the adolescents and their parents as well as the pain characteristics were assessed. Descriptive statistics, multinomial logistic regression, and regression models were used to describe the characteristics of the pain and its predictive factors. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, Boggero et al (2015) reported a smaller prevalence of pain among the elderly [ 66 ]. In a study in Iran, the number of the adolescents who experienced pain was higher in the 12–15 age group compared to the 16–21 age group [ 67 ]. The discrepancy between the findings of the above-mentioned studies can be attributed to the studies’ use of different pain scales.…”
Section: Discussionmentioning
confidence: 99%
“…However, Boggero et al (2015) reported a smaller prevalence of pain among the elderly [ 66 ]. In a study in Iran, the number of the adolescents who experienced pain was higher in the 12–15 age group compared to the 16–21 age group [ 67 ]. The discrepancy between the findings of the above-mentioned studies can be attributed to the studies’ use of different pain scales.…”
Section: Discussionmentioning
confidence: 99%
“…The IASP defines chronic pain as "pain that persists or recurs for longer than 3 months" [37]. For the purpose of this study, we operationally defined the presence of chronic pain as the self-reported experience of recurrent or persistent pain for three or more months and a frequency of at least weekly [38][39][40][41][42]. This definition was chosen because it is the most commonly used and can therefore be compared with other studies from the field [9,12].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Average scores of 3, 6, and 8 on the NRS-11 correspond to mild, moderate, and severe pain levels, respectively [46]. The NRS-11 has been used in a number of pain-related pediatric epidemiological studies [40][41][42].…”
Section: Plos Onementioning
confidence: 99%
“…CP is experienced by 46% of individuals in Sweden ( Jakobsson, 2010 ), 20.5% of people in the USA ( Yong et al, 2022 ), 34.9% of people in Hong Kong ( Wong and Fielding, 2011 ), 18.9% of people in Canada ( Schopflocher et al, 2011 ), 35% to 51% of people in the UK ( Fayaz et al, 2016 ), 23% to 76% of people in Brazil ( Aguiar et al, 2021 ), 39.3% of people in Japan ( Inoue et al, 2015 ) and 46.4% of people in Saudi Arabia ( Almalki et al, 2019 ). Additionally, studies conducted in Iran reported a prevalence of 23.7% for CP ( Shaygan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%